DEPRESSÃO NO PÓS-PARTO E ESTADO NUTRICIONAL INFANTIL NO SEGUNDO MÊS DE VIDA - Ethel Cristina Souza Santos (Universidade do Estado do Rio de Janeiro, 2013)
INTRODUCTION: Chances of illness and mortality are higher in children with inadequate nutritional status (NS) in the first months of life. Risk factors for unsatisfactory NS include maternal psychosocial aspects such as anxiety, postpartum depression (PPD) and lack of social support. However, there are few studies on the role of these factors in determining infant NS and results are controversial. OBJECTIVE: To investigate the relationship between postpartum depression and unsatisfactory infant nutritional status in the second month of life. METHODS: This is a cross-sectional survey with 466 babies at two months of age (mean = 65 days; DP=0.5) from basic healthcare units in Rio de Janeiro, RJ, conducted from June 2005 to December 2009. To compose the outcome, weight-for-age means were expressed in z scores and compared with information from the new reference curve of WHO (2006) for children aged less than five years. Children with z score below -2 were classified as having unsatisfactory nutritional status, low weight-for-age, and children with z score above +2 as excess weight-for-age. Information relating to PPD was obtained through the application of the Portuguese version of EPDS (Edinburgh Postnatal Depression Scale). Analyses of the associations between PDD and the outcomes were conducted via multinomial logistic regression models, based on estimates of crude and adjusted odd ratios (OR) and their respective 95% confidence intervals (CI 95). RESULTS: The sample revealed mean z scores of 0.22 for weight-for-age; 4.51% (n=21) showed low weight-for-age; and 1.72% (n=8) excess weight-for-age. The prevalence of depression was 27.6%. In the crude analyzes, children of depressed mothers were 2.45 times more likely (OR=2.45; C.I. 95%=1.01-5.93; p-value=0.050) to have low weight-for-age and 0.38 times more likely to have excess weight-for-age (OR=0.38; C.I. 95%=0.04-3.17; p-value =0.38) than children of non-depressed mothers. After adjustment for birth weight, environmental conditions, possession of utensils, gestational week, mother's age, mother's educational background, the association between depression and infant nutritional status did not present statistical significance (OR=2.39; C.I. 95%=0.74-7.71; p-value>0.05). CONCLUSION: PPD was associated with low weight-for-age but this association loses significance when variables such as low birth weight and prematurity, which are key factors in the genesis of growth at this stage of life, are taken into consideration.